2016
DOI: 10.5665/sleep.5734
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence with Employer-Mandated Sleep Apnea Treatment and Increased Risk of Serious Truck Crashes

Abstract: A commentary on this article appears in this issue on page 961.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 23 publications
2
88
0
Order By: Relevance
“…PAP is established, effective, and the most studied mode of treatment. Treatment with PAP reduces crash risk, 15,16,79 improves health, and decreases mortality, as discussed previously.…”
Section: Task Force Recommendations: Pap Versus Non-pap Therapiesmentioning
confidence: 93%
See 3 more Smart Citations
“…PAP is established, effective, and the most studied mode of treatment. Treatment with PAP reduces crash risk, 15,16,79 improves health, and decreases mortality, as discussed previously.…”
Section: Task Force Recommendations: Pap Versus Non-pap Therapiesmentioning
confidence: 93%
“…[51][52][53]55 No trials have explored the reasons for PAP non-adherence in this group, or ways to address it. Programs that mandate treatment, 6,16 however, such as the one by Schneider, have shown that adherence improves crash rates. 16 Therefore, a recommendation for PSG using existing guidelines yields high rates of positive diagnoses, suggesting that the BMI threshold of ≥ 35 kg/m 2 leaves high numbers of atrisk drivers untested.…”
Section: Consensus -Based Osa Screening Gui Delines Likely Capture Onmentioning
confidence: 99%
See 2 more Smart Citations
“…Over a ten year span from 2004 to 2013, it has been estimated that 3,133 to 8,952 deaths and 77,000 and 220,000 serious injuries have resulted from sleepy operators of commercial motor vehicles, many of whom most likely had undiagnosed and untreated OSA. (6) Given the severe consequences of unrecognized OSA on public safety and the high prevalence of unrecognized OSA among operators of trains, buses and commercial trucks, the imperative to screen and treat these persons for OSA is high. The advisory boards to the Federal Motor Carrier Safety Administration (FMCSA)have recommended that commercial truck drivers be screened for OSA if their body mass index is > 40 kg/m 2 , or >33 kg/m 2 and have 3 or more conditions or findings associated with OSA, but adoption of these recommendations has not occurred.…”
mentioning
confidence: 99%